Netralitas Mahkamah Internasional Dalam Menyelesaikan Sengketa Kuil Preah Vihear Antara Thailand Dan Kamboja - Arya Putra, Muhammad Rangga (Peneliti.net, 2024)
The international court is the last place that countries in the world turn to when they experience deadlock in resolving the conflict they are experiencing. As a court that adjudicates problems at the international level, it certainly has a significant role and contribution to resolving a case or conflict that is currently occurring. This research uses normative and historical legal analysis methods with a qualitative approach to examine the ICJ decision in this case. This research found that the ICJ attempted to remain neutral in resolving this dispute by considering the legal arguments of both parties objectively and impartially. The ICJ also considered historical and archaeological evidence submitted by both countries. This research concludes that the ICJ's neutrality in resolving the Preah Vihear Temple dispute is questionable. Although the ICJ attempted to remain objective and impartial, its ruling did not satisfy either side. This shows that the ICJ's neutrality in resolving disputes between countries may be difficult to achieve, especially in cases involving struggles over territory and national identity.